Effect of local youth-access regulations on progression to established smoking among youths in Massachusetts. Issue 2 (30th March 2007) - Conley Thomson, Carey; Hamilton, William L; Siegel, Michael B; Biener, Lois; Rigotti, Nancy A
Abstract : Objective: To test whether community-level restrictions on youth access to tobacco (including both ordinances and enforcement) are associated with less smoking initiation or less progression to established smoking among adolescents. Design: Prospective cohort study of a random sample of adolescents in Massachusetts whose smoking status was assessed by telephone interviews at baseline and 2-year follow-up, and linked to a state-wide database of town-level youth-access ordinances and enforcement practices. Participants: A random sample of 2623 adolescents aged 12–17 years who lived in 295 towns in Massachusetts in 2001–2 and were followed in 2003–4. Main outcome measures: The relationship between the strength of local youth access restrictions (including both ordinances and level of enforcement) and (1) never-smokers' smoking initiation rates and (2) experimenters' rate of progression to established smoking was tested in a multilevel analysis that accounted for town-level clustering and adjusted for potential individual, household and town-level confounders. Results: Over 2 years, 21% of 1986 never-smokers initiated smoking and 25% of 518 experimenters became established smokers. The adjusted odds ratio (OR) for smoking initiation was 0.89 (95% CI 0.61 to 1.31) for strong versus weak youth-access policies and 0.93 (95% CI 0.67 to 1.29) for medium versus weak policies. The adjusted OR for progression to established smoking among adolescents who had experimented with smoking was 0.79 (95% CI 0.45 to 1.39) for strong versus weak local smoking restrictions and 0.85 (95% CI 0.50 to 1.45) for medium versus weak restrictions. Conclusions: This prospective cohort study found no association between community-level youth-access restrictions and adolescents' rate of smoking initiation or progression to established smoking over 2 years.